An Analysis of the Administrative Governance of the Probolinggo Maron Suko Nutrition Fulfillment Service Unit (SPPG) in Enhancing the Effectiveness of the Free Nutritious Meal Program (MBG) in Maron District, Probolinggo Regency - Siti Marwiyah; Eko Yudianto; Antoniyo Firnanda (The Future of Education Journal, 2026)
The Free Nutritious Meal Program (MBG) is a government initiative designed to improve students' nutritional intake while supporting human resource development. The effectiveness of this program largely depends on the quality of administrative governance implemented by the Nutrition Fulfillment Service Unit (SPPG) as the local executing agency. This study aims to examine the administrative governance practices of SPPG Probolinggo Maron Suko in enhancing the effectiveness of the MBG Program in Maron District, Probolinggo Regency. A descriptive qualitative approach was employed in this research. Data were collected through field observations, in-depth interviews, and documentation involving SPPG administrators, distribution personnel, school representatives, and program beneficiaries. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and method triangulation. The findings indicate that the administrative governance of SPPG has contributed positively to the effectiveness of the MBG Program through a clear division of responsibilities, effective stakeholder coordination, and well-structured operational procedures. The dimensions of reliability, responsiveness, assurance, and empathy were implemented effectively. However, the tangible dimension still faces challenges related to limited storage facilities and the suboptimal use of information technology. In addition, shortages of human resources, fluctuations in food prices, and changes in the number of beneficiaries remain significant challenges. Therefore, strengthening administrative digitalization and improving human resource capacity are essential to ensure the sustainability of the MBG Program.